Digital literacy of biology science teacher in learning during the covid-19 pandemic - Uswatun Hasanah; Aminuddin Prahatama Putra; Badruzsaufari Badruzsaufari (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The Challenges of 21st Century Education in the digital era 4.0 require the learning process to follow digitalization. Since 2019 the world has been hit by the Covid-19 pandemic, and this condition has made the government issue an online distance learning policy. So that digital literacy competence is an urgent need for teachers to carry out learning. The study aims to describe the level of digital literacy and the character of each level of digital literacy of Biology Science teachers in learning during the Covid-19 pandemic at MTsN 2 Kapuas. The research method is descriptive qualitative with three people of the research subject. The research instrument includes the main instrument of the researcher himself and the supporting instrument of the teacher's written sheet (LTG). The level of digital literacy is categorized based on a hypothetical theory with five levels, namely LDGPP 4 (very high), LDGPP 3 (high), LDGPP 2 (medium), LDGPP 1 (low) and LDGPP 0 (very low). The results showed that Biology Science teachers' digital literacy level in learning during the Covid-19 pandemic at MTsN 2 Kapuas consisted of two levels, namely LDGPP 4 (very high) and LDGPP 3 (high). The teacher's high level of digital literacy is strength to produce students with a high level of digital literacy as well.Abstrak Tantangan Pendidikan Abad 21 era digital 4.0 menuntut proses pembelajaran mengikuti digitalisasi. Sejak tahun 2019 dunia dilanda pandemi Covid-19, kondisi ini membuat pemerintah mengeluarkan kebijakan pembelajaran jarak jauh secara online. Sehingga kompetensi literasi digital menjadi kebutuhan mendesak yang harus dimiliki guru dalam melaksanakan pembelajaran. Penelitian bertujuan untuk mendeskripsikan tingkat literasi digital dan karakteristik setiap tingkat literasi digital guru IPA Biologi dalam pembelajaran masa pandemi Covid-19 di MTsN 2 Kapuas. Metode penelitian adalah deskriptif kualitatif dengan tiga orang subjek penelitian. Instrumen penelitian meliputi instrumen utamanya peneliti sendiri dan instrumen pendukungnya lembar tertulis guru (LTG). Tingkat literasi digital dikategorikan berdasarkan teori hipotetik dengan lima tingkatan, yaitu LDGPP 4 (sangat tinggi), LDGPP 3 (tinggi), LDGPP 2 (sedang), LDGPP 1 (rendah) dan LDGPP 0 (sangat rendah). Hasil penelitian menunjukkan tingkat literasi digital guru IPA Biologi dalam pembelajaran pada masa pandemi Covid-19 di MTsN 2 Kapuas terdiri dari dua tingkatan yaitu LDGPP 4 (sangat tinggi) dan LDGPP 3 (tinggi). Level literasi digital guru yang tinggi merupakan kekuatan untuk menghasilkan peserta didik dengan level literasi digital yang tinggi pula.